2016
DOI: 10.5603/gp.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of emotional problems and mood disorders in women with polycystic ovary syndrome

Abstract: Objectives: The aim of the study was to assess the prevalence and severity of emotional problems among Polish women with polycystic ovary syndrome (PCOS) and seek factors which increase the risk of their occurrence. Material and methods:The study group consisted of 82 women (aged 18-48), who were diagnosed with PCOS based on the Rotterdam criteria. During hospitalization, the patients completed a number of questionnaires, providing their sociodemographic data and information concerning the inconvenience of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In addition, one study reported higher HOMA‐IR scores in PCOS with depression compared to PCOS without depression after controlling for BMI 33 . However, few other researchers reported no relationship between HOMA‐IR, insulin levels, FG and psychological symptoms 22,34 . In our study, we could not find any significant correlation between IR and psychiatric scores.…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, one study reported higher HOMA‐IR scores in PCOS with depression compared to PCOS without depression after controlling for BMI 33 . However, few other researchers reported no relationship between HOMA‐IR, insulin levels, FG and psychological symptoms 22,34 . In our study, we could not find any significant correlation between IR and psychiatric scores.…”
Section: Discussioncontrasting
confidence: 82%
“…According to studies, women with PCOS are more likely to suffer from mood disorders than healthy ones [10,11]. Also, the prevalence of depression is higher 4-5 times in these patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a disabling endocrinopathy affecting approximately 6–10% of women of childbearing age ( 1 ). The condition is multifactorial and often difficult to diagnose due to the existence of different diagnostic criteria ( 2 ), mainly based on the presence of a combination of clinical signs of anovulation or menstrual irregularities, polycystic ovaries and androgen excess ( 3 ).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%